A escrita feminina cearense do século XIX: uma perspectiva de análise da poesia de Ana Nogueira e Francisca Clotilde - Castro, Carla Pereira de (2021)
This study analyses how the marks that singularize the writing of female authorship appear in the poetry of Ana Nogueira Batista (1870-1967) and Francisca Clotilde Barbosa Lima (1862-1935) published in the 19th century and that are scattered in newspapers, magazines and almanacs of that time. As a reference for analysis, we resorted to the characteristics of female writing pointed out by Lúcia Castello Branco in the work A Mulher Escrita, originally published in 1989 in partnership with Ruth Silviano Brandão. The research also is guided by theoretical studies on Ceará literature and, mainly, on the trajectory and affirmation of women in the world of letters, whether on a world scale or at the national/local level. In this perspective, the following authors should be highlighted: Sânzio de Azevedo (1976), Mozart Soriano Aderaldo (1987), Antônio Sales (1922), Cecília Maria Cunha (2008), Heloísa Buarque de Hollanda and Lucia Nascimento Araújo (1993), Branca Moreira Alves and Jacqueline Pitanguy (1985), Greicy Pinto Bellin (2011), Hélène Cixous (1976), Constância Lima Duarte (1990; 2003) and June Edith Hahner (1981). Through the rescue and analysis of the selected poems, we highlighted two female writers from Cearáwho did not accept to remain on the margins of society, sinceboth participated actively in the intellectual and social movements such as Clube Literário (Literary Club), Padaria Espiritual (Spiritual Bakery)and the struggles for the freedom of slaves. So, the rescue of the two poets proves to be important since it contributes to fill a gap caused by the still scarce number of studies on great Brazilian femalewriters silenced by the androcentric tradition of our national letters.